Practical Spirituality and Human Development Transformations in Religions and Societies (Springer Singapore, 2018)
In a world where the rise of the religious in politics and the public sphere is often accompanied by violence and religious fundamentalism, this book considers the increasing relevance of movements of practical spirituality from multiple traditions and domains of life which strive to transform violence into positive human relations. It examines how spirituality can contribute to human development, social transformations and planetary realizations, urging us to treat each other, and our planet, with evolutionary care and respect. Trans-disciplinary and trans-paradigmatic to its very core, this text opens new pathways of exploration and action for both scholarship and discourse and offers an invaluable companion for scholars across religious studies, cultural studies and development studies.